Evaluation the effectiveness of in-sewer purification system and its application in Vietnam condition : Luận văn ThS. Kỹ thuật hoá học, vật liệu, luyện kim và môi trường: 605203 - Duong, Thu Thuy (2019)
Vietnam is now striving for global i activities, education, which are the implementation of the Sustainable Deve the report of Vietnam Ministry of Plan achieved many achievements after 1 Development Goals (MDGs) (Country organized before SDGs. However, t environment is currently quite difficult the reduction of environmental pollution Being a developing country with a youn many challenges for Vietnam. The popu This puts pressure on the environment the generation of domestic wastewate system in Vietnam that is still not mod and sewerage are the combined system development stages of the country, t deteriorating facilities causing inca uncontrolled wastewater volume, whic incapacity drainage systems without tre objectives to focus in Vietnam water fie Currently, Vietnam is striving to achie 2030 (Bộ Xây dựng, 2011). In the conte study to evaluate the applicability of a sewer purification. The technology, on advantage of saving time on constructi acting as a preliminary treatment step be (Wastewater treatment plants). Here, I conducted following studies to evaluate the applicability of the in-sewer purification technology with the particular objectives below: -To review the pilot studies on in-sewer purification technology conducted by Sekisui Chemical Co. Ltd (Chapter 2). -To examine the mechanisms of water quality improvement using a laboratory scale in-sewer purification system (Chapter 3). -To evaluate the feasibility by a primitive sewer design study (Chapter 4).